A gestão de projetos e a maturidade da indústria 4.0: a proposição de um modelo - Teixeira, Silvio Cesar Alves (2020)
With the growth of Industry 4.0, companies need to understand the stage of maturity and how they can move forward. In this context, the maturity models are an important tool in that trajectory of companies’ transformation in different and sectors. Given that Industry 4.0 initiatives often start through projects and the Project Management can be a driving force for the advancement of Industry 4.0 maturity. Thus, the present research has an objective to propose a model that assesses how project management contributes to the maturity of industry 4.0. This research is divided into 4 phases. The first phase explored the maturity studies of Industry 4.0 and maps the existing maturity models and their characteristics. In the second phase, it explores the characteristics of Industry 4.0 projects. The third phase explores in-depth interviews with 12 Project Managers who work specifically with Industry 4.0 Projects, to obtain information collection. The last phase aimed to validate the characteristics mapped with executives and specialists in the area of Project Management and academic specialists in Industry 4.0. This research resulted in a model that demonstrates how Project Management contributes to the Maturity of Industry 4.0 and, consequently, to its progress, and which can also be used as a guide for the project community.